ANALISIS KEPUASAN TERHADAP LAYANAN APLIKASI DOLTINUKU DENGAN MENGGUNAKAN METODE STRUCTURAL EQUATION MODELING-PARTIAL LEAST SQUARE (SEM-PLS) - Ul Haq, Hasna Faridah Dhiya; Hakim, Arief Rachman; Suparti, Suparti (Jurnal Gaussian, 2023)
Doltinuku is an application that is used to buy and sell products and services online from MSME in Gedawang, Banyumanik Sub-District, Semarang City which was just launched in June 2021. Because this application is still new, this application needs to be developed by looking at users' satisfaction. This study wants to determine Doltinuku customer satisfaction using Structural Equation Modeling-Partial Least Square (SEM-PLS) method. PLS is an alternative method of SEM that is able to handle variance-based problems. In this study, customer satisfaction is measured through variables such as Quality, Information, Reputation, and Trust. Based on the results of the analysis, variables that have a significant effect on customer satisfaction are variable Quality and Reputation and have influence of 70.9% on satisfaction whose value is obtained from the R2 value. Then the variables that have no significant effect are variable Information and variable Trust.